Breastfeeding, 'tainted' love, and femmephobia: containing the 'dirty' performances of embodied femininity. Issue 1 (2nd January 2022) - Whiley, Lilith A.; Stutterheim, Sarah; Grandy, Gina
ABSTRACT: In this conceptual analysis, we theorise breastfeeding as an embodied 'dirty' performance of femininity and draw on Hoskin's (2019a) work on femme theory to propose that women who breastfeed in public, who do so for an 'extended' time, and who enjoy it are subject to femmephobic attacks. We integrate three streams of literature to unsettle the 'taint' of breastfeeding. We first theorise breastfeeding as an act of femininity where women perform gender trouble in line with Butler's work. We also draw on Douglas' work on 'dirt' and Rivera's work on emotional 'dirty' work to theorise that 'taint' is one way in which society stigmatises the phenomenon of breastfeeding. Specifically, we propose that embodied breastfeeding evokes 'tainted' emotions. We then draw on Schippers' work on 'containing' pariah forms of femininity (lest they 'contaminate' patriarchy) by showing how femmephobic stigmatisation limits breastfeeding women's corporeality and presence in shared spaces.